Seismo‐tectonic behavior of the Pernicana Fault System (Mt Etna): A gauge for volcano flank instability?. Issue 8 (13th August 2013) - Ruch, J.; Pepe, S.; Casu, F.; Solaro, G.; Pepe, A.; Acocella, V.; Neri, M.; Sansosti, E.
Abstract : [1] Flank instability at basaltic volcanoes is often related to repeated dike intrusions along rift zones and accompanied by surface fracturing and seismicity. These processes have been mostly studied during specific events, and the lack of longer‐term observations hinders their better understanding. Here we analyze 20 years of deformation of the Pernicana Fault System (PFS), the key structure controlling the instability of the eastern flank of Mt. Etna. We exploit East‐West and vertical components of mean deformation velocity, as well as corresponding time series, computed from ERS/ENVISAT (1992–2010) and COSMO‐SkyMed (2009–2011) satellite radar sensors via Synthetic Aperture Radar Interferometry techniques. We then integrate and compare this information with field, seismic, and leveling data, collected between 1980 and 2012. We observe transient displacements accompanied by seismicity, overprinted on a long‐term background eastward motion ( 2 cm/yr). In the last decades, these transient events were preceded by a constant amount of accumulated strain near the PFS. The time of strain accumulation varies between a few years and a few decades, also depending on magma emplacement within the nearby North East Rift, which may increase the strain along the PFS. These results suggest that the amount of deformation near the PFS may be used as a gauge to forecast the occurrence of instability transients on the eastern flank of Etna. In this context, the PFS may provide an ideal, small‐scale structure to test the relations between strain accumulation, stress loading, and seismic energy release. Key Points: Understanding flank instability using InSAR time series at Etna Threshold of accumulated deformation before seismo‐tectonic transients Deformation field as a gauge to assess seismic and volcanic activity